Learning Strategies Instruction: A Proposal for Encouraging Autonomous Learners - Hernández Gaviria, Fanny; Ramirez, Alexander (Colombian Applied Linguistics Journal, 2024)
This reflective paper aims at disseminating a proposal for instruction to promote learning strategies in the foreign language classroom. The proposal was constructed based on the results of two action-research projects conducted at the Foreign Language Teacher Education Program (English – French) at Universidad del Valle, in Cali, Colombia. The results of these projects suggest that the implementation of learning strategies requires a specific sequence to develop learner autonomy and that finding the right dosage of strategies to cover in a course is paramount for their successful acquisition and implementation. Thus, the authors propose an adaptable instruction model that considers the findings of their research experiences. In this paper, the authors claim that while some strategies can be developed spontaneously throughout the learning process, some other strategies are more difficult to grasp, and therefore they require explicit instruction in just the right amount.